Pure Mathematics 2 & 3 - "Hugh Neill : Douglas Quadling" (Cambridge University Press: Cambridge, 2002)
Pure Mathematics 2 corresponds to units P2 and P3. It covers algebra, logarithmic and exponential functions, trigonometry, differentiation, integration, numerical solution of equations, vectors, differential equations and complex numbers.
Keywords: Mathematics Mathematics Problems, exercises